MEMBANGUN KEDISIPLINAN SISWA DALAM PANDANGAN HINDU - Ketut Bali Sastrawan (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2018)
Teachers are human figures who occupy positions and play an important role ineducation. Teachers in the context of Hinduism have a very noble position. Even the holy book ofHinduism describes a lot about how a student must respect his teacher. The form of discipline ofa student at school can be seen from how much he appreciates his teacher. Schools should beused as a place for students to hone their discipline. Once the importance of a student to respectthe teacher according to Hinduism, requires the school to make a rule that supports it. Synergybetween parents and teachers in building student discipline is very necessary. Teachers in schoolsplay a role in controlling their discipline in school while parents at home play a role in monitoringstudents' discipline at home.